Silent Pasts and a Reconfigured Present in Histories of Chinese (New) Opera - Annie Yen-Ling Liu (Musica Docta)
The ‘New Chinese Opera’, which emerged in the 1940s, has become a significant part of the performance repertoire, a ‘hot’ research topic and an indispensable subject of historical surveys of Chinese music. The subject matter of these operas ranges from historical events (as in Honghu Red Guards of 1958) to stories drawn from classic Chinese novels (as in Camel Xiangzi of 2014). Critical and aesthetic reception has focused on the dominance of realistic subject matter in this form and the concern of its producers to reach a wide audience. This emphasis on the marketability of art reflects how deeply rooted secularisation and utility are in contemporary Chinese culture. This paper examines a third theme of aesthetic discourse that is particularly present in historical narratives of Chinese opera: the struggle to distance Chinese opera from Western models. The image of ‘opera’ that emerges in these accounts reconfigures the form for contemporary use, with the result that the history of Western opera as an agent is absent - or, in the case of dramaturgical models and influences, distorted.